Using Targeted Liquid Chromatography-Tandem Mass Spectrometry to Rapidly Detect β-Lactam, Aminoglycoside, and Fluoroquinolone Resistance Mechanisms in Blood Cultures Growing E. coli or K. pneumoniae - Foudraine, Dimard E.; Dekker, Lennard J. M.; Strepis, Nikolaos; Nispeling, Stan J.; Raaphorst, Merel N.; Kloezen, Wendy; Colle, Piet; Verbon, Annelies; Klaassen, Corné H. W.; Luider, Theo M.; Goessens, Wil H. F. (Frontiers in Microbiology, 2022)
New and rapid antimicrobial susceptibility/resistance testing methods are required for bacteria from positive blood cultures. In the current study, a multiplex targeted liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay was developed and validated for the detection of beta-lactam, aminoglycoside and fluoroquinolone resistance mechanisms in blood cultures growing E. coli or K. pneumoniae complex. Selected targets were the beta-lactamases SHV, TEM, OXA-1-like, CTX-M-1-like, CMY-2-like, chromosomal E. coli AmpC (cAmpC), OXA-48-like, NDM, VIM and KPC, the aminoglycoside modifying enzymes AAC(3)-Ia, AAC(3)-II, AAC(3)-IV, AAC(3)-VI, AAC(6’)-Ib, ANT(2”)-I and APH(3’)-VI, the 16S-RMTases ArmA, RmtB, RmtC and RmtF, the quinolone resistance mechanisms QnrA, QnrB, AAC(6’)-Ib-cr, the wildtype QRDR of GyrA, and the E. coli porins OmpC and OmpF. The developed assay was evaluated using 100 prospectively collected positive blood cultures, and 148 negative blood culture samples spiked with isolates previously collected from blood cultures or isolates carrying less prevalent resistance mechanisms. The time to result was approximately 3 hours. LC-MS/MS results were compared with whole genome sequencing and antimicrobial susceptibility testing results. Overall, there was a high agreement between LC-MS/MS results and WGS results. In addition, the majority of susceptible and non-susceptible phenotypes was correctly predicted based on LC-MS/MS results. Exceptions were the predictions for ciprofloxacin and amoxicillin/clavulanic acid which matched with the phenotype in 85.9 % and 63.7 % of the isolates, respectively. Targeted LC-MS/MS based on parallel reaction monitoring can be applied for the rapid and accurate detection of various resistance mechanisms in blood cultures growing E. coli or K. pneumoniae complex.